STRATEGI MENINGKATKAAN MOTIVASI SISWA DALAM MENGHAFAL AL-QURAN JUZ 30 (STUDI KASUS MTs NURUL HUDA MALANG) - Nadia Eka Tania; Anwar Sa’dullah; Lia Nur Atiqoh Beladina (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aimss to determinee thee teacher’s strategy in increasing student motivatiion in memorizing Al-Qur’an juz 30 (Case study of MTs Nurul Huda Malang). The problem faced is that there are some student who are lazy and lack enthusiasm in tadarus Al-Qur’an juz 30 and the impact makes it difficult for students to memorize and worry that they cannot reach the targets set by the in madrasah. Sources of data obtained from suvervisors and several students. This study uses a qualitative method, where documents is obtained based on the results of interviews, observation, and documentation. Which is analyzed by documents reduction, documents presentation, drawing conclusions and verifying the conclusions. The results of this study indicatr that the teacher uses several strategies that have been designed and applied using the drill method so that the teacher succeds in getting a good response from students.